Mammalian SWI/SNF Enzymes and the Epigenetics of Tumor Cell Metabolic Reprogramming - Nickerson, Jeffrey A.; Wu, Qiong; Imbalzano, Anthony N. (Frontiers in Oncology, 2017)
Tumor cells reprogram their metabolism to survive and grow in a challenging microenvironment. Some of this reprogramming is performed by epigenetic mechanisms. Epigenetics is in turn affected by metabolism; chromatin modifying enzymes are dependent on substrates that are also key metabolic intermediates. We have shown that the chromatin remodeling enzyme BRG1, an epigenetic regulator, is necessary for rapid breast cancer cell proliferation. The mechanism for this requirement is the BRG1-dependent transcription of key lipogenic enzymes and regulators. Reduction in lipid synthesis lowers proliferation rates which can be restored by palmitate supplementation. This work has established BRG1 as an attractive target for breast cancer therapy. Unlike genetic alterations, epigenetic mechanisms are reversible, promising gentler therapies without permanent off-target effects at distant sites.